PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI PERILAKU NEGATIF SISWA MTs PUI SEGERAN INDRAMAYU - Asep Kurniawan (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2019)
Students of Madrasah Tsanawiyah PUI Segeran Indramayu had negative behavior. This was in stark contrast to the views of the surrounding community. They thought that students who study in religious education institutions, such as Madrasah Tsanawiyah, had better behavior than students who study in secondary schools. It was because Madrasah Tsanawiyah is an Islamic school. The purpose of the study was to reveal in depth about the role of Islamic Education teachers in overcoming students’ negative behavior. This study used a qualitative approach. The research findings showed that students’ negative behavior are lighting firecrackers in class, not wearing uniforms, not working on teachers’ assignments, chatting and joking in learning, drawing motorcycle gang names in books, singing persib songs, making and playing paper airplane. This behavior was influenced by internal and external factors. In this case, Islamic education teachers carried out preventive actions, namely: congregational prayers, commemoration of Islamic holidays, Pesantren Ramadan, Islamic education teachers’ exemplary, empowering extra organizations, mentoring, reminding, advising, and inviting dialogue, weekly religious studies. Repressive measures were to provide penalties toward educating not oppressive, and give more assignments than other students. Curative actions, namely: (1) general actions, they included: (a) Advice and reprimand with a religious approach. (b) Provide reasonable special attention to problematic students. (c) Cooperate with parents of problematic students in overcoming their negative behavior. (2) (2) Special actions through a case-by-case individual approach.